The physical performance uncertainty facing lacrosse officials for the Los Angeles Olympics in 2028 - Ripley, N.; Fahey, J.; Quinn, M. (Strength and Conditioning Journal, 2025)
Sixes Lacrosse (SL) is a newly developed format of field lacrosse (FL) to be included in the 2028 Los Angeles Olympics. Officials are crucial to upholding the rules of the game and maintaining player safety. There is currently no evidence of the match demands of lacrosse officials. The purpose of this narrative review is to explore the match demands of officials of other team sports to enable comparison with expected demands for officials in SL. Based on the literature on other team sports, SL officials will likely cover lower total distances than FL; however, this will likely be at higher relative intensities. International SL tournaments are currently designed to be held over a short period; hence, match officials should be prepared to cope with the volume with preparation and recovery strategies. This review highlights that research is needed to identify the expected demands of SL for match officials to provide appropriate training guidelines to maximize performance. Of similar importance, developing a specific and appropriate testing battery needs to be designed that matches the demands of the sport at the highest level, which could aid practitioners and the world governing body in providing future recommendations for lacrosse officials.